MO1027EFFICACY OF CALCINEURIN INHIBITORS IN CHILDREN WITH MONOGENIC STEROID-RESISTANT NEPHROTIC SYNDROME. (29th May 2021) - Prikhodina, Larisa; Papizh, Svetlana; Povolotskaya, Inna
Abstract: Background and Aims: Monogenic causes of steroid-resistant nephrotic syndrome (SRNS) have been reported for up to one-third of children depending on age of the disease onset. Immunosuppressive treatment of genetic SRNS with calcineurin inhibitors (CNIs) is still controversial. The aim of the study was to investigate the efficacy of CNIs with focus on inducing remission and long-term kidney function in children with monogenic SRNS. Method: Retrospective analysis of efficacy CNIs in five children (2M/3F) with monogenic SRNS was performed. Kidney biopsy prior CNIs revealed FSGS (n=4) and MCD (n=1). The initial cyclosporine (CsA) dose was 5 mg/kg/24h to keep a target level of 80-150 ng/ml and tacrolimus (TAC) - 0.1 mg/kg/24h to achieve a target level of 5-10 ng/ml. CsA took all 5 patients with subsequent switching to TAC in 2 children due to cosmetic side effects. The median follow-up period was 165.0 (IQR: 59.0; 185.5) months. Next generation sequencing (NGS) was used for identification of pathogenic variants in all patients. Results: The median age at onset of monogenic SRNS was 33.0 (IQR: 16.5; 63.0) months. 2/5 (40%) patients presented with acute SRNS, 1/5 (20%) child with infantile NS, 1/5 (20%) - with isolated nephrotic range proteinuria with hypoalbuminemia and 1/5 (20%) - with NS and extrarenal features of Nail-Patella syndrome. NGS identified previously described pathogenic variants in all 5 children, including NPHS2 homozygous c.28dup (p.Glu87Ter) (n=1), NPHS2 compound heterozygous c.868G>A (p.Val290Met) in combination with c.686G>A (p.Arg229Gln) (n=1), LMX1B heterozygous c.788T>G (p.Val263Gly) (n=1), LMX1B heterozygous c.737G>A (p.Arg246Gln) (n=1), and COL4A3 heterozygous c.2962G>A (p.Gly988Arg) variant (n=1). The median time from diagnosis to initiation of CNIs treatment was 72.0 (IQR: 33.0; 93.0) months. CNIs induced complete remission in 2/5 (40%) patients, presented with acute SRNS, including one girl with MCD due to NPHS2 compound heterozygous variants with mutation-dependent pathogenicity of one (p.R229Q) of them and one boy with FSGS due to COL4A3 heterozygous variant (n=1). Partial remission was induced by CNIs in 2/5 (40%) girls with FSGS due to LMX1B heterozygous variants with isolated SRNS (n=1) and Nail-Patella syndrome (n=1). The median duration of CNIs treatment to obtain complete or partial remission was 13.5 (IQR: 6.8; 15.8) months. Acute CNIs-associated nephrotoxicity had 2 patients with LMX1B variants. At the last follow up full and partial responders to CNIs treatment aged of 16.5 (IQR: 11.8; 17.5) years had CKD-1 (n=3) and CKD-2 (n=1). 1/5 (20%) boy with NPHS2-associated infantile NS was CNI resistant and developed CKD-5 at the age of 6.5 years with subsequent living related kidney transplantation. Conclusion: We found that 4/5 (80%) children with monogenic SRNS demonstrated partial or full response to CNIs treatment with stable long-term kidney function. We assume that CNIs might improve podocyte function by stabilization of their cytoskeleton disrupted in patients with monogenic SRNS.